Fotopoema : leitura, fruição e criação lírica em jogo - Oliveira, Rivalmir Alves de (2021)
Photopoem, a hybrid textual genre that mixes poem and photography, is a source of diversified knowledge and has been gaining space in the literary world, in schools and in virtual spaces. Its presence in classrooms, in addition to enabling students to acquire and expand knowledge about this “poetic form”, proves to be an excellent resource for encouraging reading and the production of poems. Therefore, photopoem was chosen as corpus for the development of thisthesis in the Professional Master's in Portuguese Language (PROFLETRAS/ITA), which objective to teach students of the 7th grade to read, enjoy and create photopoems, involving in this process a card game made with photos and poems. The function if the game is to be an object of learning for the class and to become an instrument for other educators, who can use it with their classes and / or even adapt it to their needs. In addition to the photopoems, the proposed methodology, which has its main characteristic of an action research, includes other poems and varied texts, from which there will be an initial investment in student reading and writing until the game and the production of photopoems by / the students. We know that reading and writing are essential learnings for the subject to expand and acquire diverse knowledge of social life and for social life because the more these skills are developed, the more the individual has the ability to act and live together in society. By inserting photography as a mediating element for reading and producing poems, the proposal presented here recognizes the importance of valuing a basic component of the reality that we live in today: the image. This aspect seeks to make this presence a stimulus for student involvement with lyrical language. Theoretically, the thesis is based on scholars such as: Sontag (1977), Candido (1996), Mauad (1996), Magnani (2001), Eco (2004), Felizardo and Samain (2007), Xavier (2009), Freitas (2016), Silva e Jesus (2011), Ramalho (2014), Gens Filho (2014), Gomes (2016), Gomes and Menezes (2016), Santos (2016), Barbosa and Leurquin (2017), from which issues related to the teaching of poetry, literary reading are discussed, textual production, the presence of technology in the school's daily life and multimodality, in addition to addressing the specificities of photography and the poem. It is expected that the elaborated game and the proposed method become didactic resources capable of contributing not only to expand the presence of the poem in the classrooms but also to give more space to contact with the genre of photopoem.